Frequent video game playing alters low-frequency event-related EEG brain oscillations - Yıldırım, Ebru; Kol, Mustafa Yusuf; Özkan, Mehmet Fatih; Doğru, Ömer Faruk; Güntekin, Bahar (Frontiers in Psychology, 2025)
IntroductionFrequent exposure to video gaming induces changes in cognitive and perceptual functions and alterations in neural structure and functioning. While frequent video gaming has been associated with positive effects in cognitive-perceptual domains, it may concurrently exert adverse impact on social–emotional functioning. This study used event-related EEG brain oscillations to investigate the effect of frequent playing video games on the visual and auditory working memory processes.MethodsThe study included 23 healthy young men participants, divided into frequent gamer and infrequent gamer groups based on their exposure to violent video games. An internet-based questionnaire was used for group classification, and the frequent gamer group consisted of participants who played more than 15 h of video games per week. EEG recordings were obtained during visual and auditory memory tasks, and participants’ anxiety levels were assessed using the State–Trait Anxiety Inventory. Event-related power spectrum and phase-locking analyses were conducted for delta, theta, and alpha frequencies.ResultsNo significant group differences were observed in behavioral performance and anxiety levels; however, there were notable electrophysiological differences. The frequent gamers exhibited lower and shorter visual delta responses compared to infrequent gamers. A left-hemisphere dominance for the frequent gamers was observed in auditory theta and alpha power, particularly in the parietal and occipital regions. Additionally, the frequent gamers showed reduced visual alpha power in posterior regions and less increase in auditory lower alpha phase-locking.DiscussionIn conclusion, the observed alterations in low-frequency event-related oscillations suggest that the frequent gamers employ distinct neurocognitive strategies during memory tasks. These strategies may reflect enhanced efficiency in specific domains such as attention and memory, despite similar behavioral performance.